Efektivitas Rancangan Program Pengembangan Self Regulation Berbasis Teknologi Informasi dalam Meningkatkan Kemampuan Mengelola Emosi (Studi pada Peserta Didik di Kelas XI SMKN 2 Padang) - Chenia Emelda Putri; Helma Helma; Rici Kardo (Journal on Education, 2023)
This research is motivated by the phenomenon of students who have not been able to have the ability to manage emotions. The aims of this study were: (1) Profile of self-regulation of students before treatment in the experimental group and control group, (2) Profile of self-regulation of students after treatment in the experimental group, (3) Effectiveness of the development program Information technology (IT)-based self-regulation improves the ability to manage students' emotions. This study uses a quantitative approach, the type of research is experimental. The location of this research is at SMKN 2 Padang. The samples in this study were 35 students in class XI BPD (Digital) (experimental group) and 35 students in class XI RPL (control group). The data collection technique used is a questionnaire. The data analysis technique used is Ancova. The results of the study found: 1) The level of self-regulation before treatment was classified as low, both in the experimental class and the control class. 2) The level of self-regulation after the treatment underwent significant changes, especially in the experimental group. 3) Information technology-based emotional intelligence development program is effective in significantly increasing the Self Regulation ability of class XI students at SMKN 2 Padang. Based on the results of this study, it is recommended for counseling teachers to be used as guidelines or input materials for implementing the Self Regulation development program in improving the ability to manage students' emotions.